Predictors of early breastfeeding cessation among HIV‐infected women in Botswana. Issue 8 (16th June 2016) - Ogwu, Anthony; Moyo, Sikhulile; Powis, Kathleen; Asmelash, Aida; Lockman, Shahin; Moffat, Claire; Leidner, Jean; Makhema, Joseph; Essex, Max; Shapiro, Roger
Abstract: Objective: Infants born to HIV‐infected women receiving antiretroviral treatment (ART) can be breastfed through at least 6 months with very low risk of HIV acquisition. We aimed to identify demographic and cultural factors that may influence mothers' willingness to breastfeed for the recommended duration. Methods: We evaluated factors associated with early cessation of breastfeeding (i.e. before 5 months post‐partum) in a randomized clinical trial evaluating different ART regimens used for prevention of mother‐to‐child transmission during breastfeeding in Botswana. Univariate and multivariable Cox regressions were used to describe predictors of early exclusive BF cessation. Results: Among 677 women who started breastfeeding, the median time to breastfeeding cessation was 178 days (IQR 150–181) and 25.1% weaned early. In multivariable analysis, urban location (aHR = 1.86 95%CI 1.27–2.73; P = 0.002), salaried employment or being a student (aHR = 2.78 95% CI 1.63–4.75; P < 0.001) and infant hospitalisation before weaning (aHR = 2.04 95% CI 1.21–3.45; P = 0.008) were independently and significantly associated with early BF cessation. Conclusions: Improved support for breastfeeding among employed mothers, especially in urban settings, may allow HIV‐infected women who are receiving ART prophylaxis to breastfeed longer.